Anticoagulation and bone marrow biopsy: is it safe to proceed?. Issue 1 (1st January 2021) - Moore, Cameron; Kotchetkov, Rouslan
ABSTRACT: Background: Bone marrow (BM) biopsy is the most common diagnostic procedure in hematology. Bleeding is an expected complication, and its risk is assumed to be increased in patients on anticoagulants. However, the effect of anticoagulation on BM biopsy safety is unclear and guidelines are lacking robust data in this regard. As such, physicians use their clinical judgement to guide periprocedural management of anticoagulation. objective: To provide the best available evidence regarding management of anticoagulation in patients who need BM biopsy. Methods: We reviewed and summarized available guidelines directing management of periprocedural anticoagulation for BM biopsy, and share our experience and practices with BM biopsy at our institution. Results: The incidence of significant hemorrhage after BM biopsy is very low (0.007–1.1%). BM biopsy is classified as having a low to moderate bleeding risk. Interrupting anticoagulation is not consistently recommended. Strategies exist to minimize bleeding risk for anticoagulated patients. Patients with myeloproliferative neoplasms can develop an acquired von Willebrand syndrome which increases their risk for bleeding and therefore require extra vigilance to ensure appropriate hemostasis. Conclusion: Withholding anticoagulation prior to BM biopsy is not routinely recommended. Instead, assessment and optimization of bleeding risk factors should be done on a patient by patient basis.